2023
DOI: 10.3389/fimmu.2023.1110292
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic risk stratification of pediatric heart transplant patients by combining HLA-EMMA and PIRCHE-II

Abstract: Human leukocyte antigen (HLA) molecular mismatch is a powerful biomarker of rejection. Few studies have explored its use in assessing rejection risk in heart transplant recipients. We tested the hypothesis that a combination of HLA Epitope Mismatch Algorithm (HLA-EMMA) and Predicted Indirectly Recognizable HLA Epitopes (PIRCHE-II) algorithms can improve risk stratification of pediatric heart transplant recipients. Class I and II HLA genotyping were performed by next-generation sequencing on 274 recipient/donor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…By focusing on specific algorithms, the study provides insights into the predictive power of these tools in identifying transplant recipients at risk of developing complications like DSA and AMR. The findings may have practical implications for clinicians, as they suggest that certain molecular mismatches could serve as early warning signs, allowing for proactive interventions to prevent or manage rejection episodes 37,38 . In summary, both studies by Mangiola et al and Ellison et al contribute significantly to the field of transplant immunology by emphasizing the importance of molecular mismatch algorithms in predicting immunological responses and clinical outcomes in pHTR.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…By focusing on specific algorithms, the study provides insights into the predictive power of these tools in identifying transplant recipients at risk of developing complications like DSA and AMR. The findings may have practical implications for clinicians, as they suggest that certain molecular mismatches could serve as early warning signs, allowing for proactive interventions to prevent or manage rejection episodes 37,38 . In summary, both studies by Mangiola et al and Ellison et al contribute significantly to the field of transplant immunology by emphasizing the importance of molecular mismatch algorithms in predicting immunological responses and clinical outcomes in pHTR.…”
Section: Discussionmentioning
confidence: 90%
“…By using HLAMatchmaker, PIRCHE, or HLA‐EMMA, some authors have found that heart and lung transplant patients with higher HLA‐DR and/or HLA‐DQ epitope mismatch loads showed an enhanced risk of poor transplant outcomes compared with other patients 20,21,32 Recenlty the studies by Mangiola et al and Ellison et al in the pediatric heart cohort, which explore the impact of various algorithms like Matchmaker, PIRCHE II, and EMMA on the development of de‐novo DSA and AMR, are important additions that should be included to provide a more well‐rounded perspective on the topic. By incorporating these recent studies and acknowledging the contributions of Nickerson and Wiebe's group, the review can offer a more up‐to‐date and comprehensive view of the role of molecular mismatch in kidney and thoracic organ transplantation, enhancing its overall quality and relevance 37,38 . In their study, Mangiola and colleagues investigated the impact of combined algorithms, including Matchmaker, PIRCHE II, and EMMA, on the development of de‐novo DSA and AMR in a large pediatric heart cohort.…”
Section: Discussionmentioning
confidence: 99%